When the World Came to Banten - Farish A Noor (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2018)
This paper aims to demonstrate that pluralism has always been part and parcel of ordinary human lives in Indonesia, and that is was the normmas far back as the sixteenth to seventeenth centuries when Muslim power was at its height in Java and the rest of the archipelago, long before themadvent of European colonial-capitalism and long before the decline ofmMuslim political-economic power. It hopes to provide a counterfactual argument that shows that cosmopolitanism and pluralism were indeed part of daily political-economic life then, and that Indonesian Muslims were in fact able to live in such a cosmopolitan environment where pluralism was not regarded as a threat or a reason for mass-scale moral panic. The opposite was the case that when Muslim economic-political power was at its height in Java, Javanese Muslims were at their most accommodating and welcoming towards foreigners of diverse ethnic, cultural, linguistic and religious backgrounds. In order to highlight such pluralism evidence, our reference will be the work of the writer Johann Theodorus de Bry, whose work Icones Indiae Orientalis was published in 1601.Keywords: Pluralism, Cosmopolitanism, Banten, Theodorus de Bry, Seventeenth Century